What role do environmental factors play in the development of neurodegenerative diseases? A narrative review - Kuszneruk, Julia; Chawrylak, Katarzyna; Kłusek, Magdalena; Kubas, Maria; Krzemińska, Katarzyna (Quality in Sport, 2024)
Introduction and purposes: Degenerative diseases of the nervous system, such as Alzheimer’s disease (AD), Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS). Environmental influences are significant contributors to the development of these conditions. The primary objective of this research was to examine key environmental factors that are suspected of their impact on the development of diseases, specifically lifestyle, medical conditions, diet and exposure to environmental pollution. Materials and Methods: A systematic literature search was conducted using PubMed and Google Scholar. The search employed terms such as ’Alzheimer’s disease,’ ’Parkinson disease,’ ’amyotrophic lateral sclerosis,’ ’environment,’ ’pollution,’ ’diet,’ ’traumatic brain injury,’ ’alcohol,’ ’obesity,’ ’lifestyle factors’. The search included articles published from 2014 to 2024. Results: Among environmental factors with regard to lifestyle choices, a healthy diet has a protective effect against these diseases, while alcohol consumption was not clearly categorised as harmful or protective. Among past illnesses, an increase in AD, PD after head injury was confirmed, but more research is required as to the impact on ALS incidence. Lipid metabolism disorders affect ALS morbidity, for the AD and PD, studies do not reach consensus. Similarly, with regard to body weight, studies do not clearly indicate whether it is relevant. On the contrary, when it comes to pollution, a lot of studies showed a correlation. Conclusion: In summary, research studies varied in size and quality, so caution must be exercised in drawing conclusions. This review suggests that there is a relationship with the environment, and future research may focus on exploring these connections.